2006
DOI: 10.1037/0735-7044.120.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

Primes and targets in rapid chases: Tracing sequential waves of motor activation.

Abstract: Single-cell recordings have indicated that visual stimuli elicit rapid waves of neuronal activation that propagate so fast that they might be free of intracortical feedback. Here, the time course of feedforward activation was traced by measuring pointing responses to color targets preceded by color primes initiating either the same or opposite response. The early time course of priming effects was strictly time locked to prime onset and depended only on properties of the primes, but was independent of the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
80
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 45 publications
9
80
0
1
Order By: Relevance
“…In several studies, Schmidt and Schmidt (2009) and Schmidt, Niehaus, and Nagel (2006) investigated the effects of unconsciously (or preconsciously) processed information on pointing movements: They found that the initial trajectory of a pointing movement is guided by feedforward-processed visual information. Interestingly, both the results obtained by Schmidt and coworkers, and the results we obtained in Experiment 3 share one critical feature: Both prosaccades and pointing movements do not require a spatial transformation or remapping of a response, and are completely stimulus-driven.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, Schmidt and Schmidt (2009) and Schmidt, Niehaus, and Nagel (2006) investigated the effects of unconsciously (or preconsciously) processed information on pointing movements: They found that the initial trajectory of a pointing movement is guided by feedforward-processed visual information. Interestingly, both the results obtained by Schmidt and coworkers, and the results we obtained in Experiment 3 share one critical feature: Both prosaccades and pointing movements do not require a spatial transformation or remapping of a response, and are completely stimulus-driven.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that visuomotor activation in response priming paradigms can be explained exclusively by successive waves of feedforward motor activation triggered by primes and targets (Schmidt, Niehaus, & Nagel, 2006). At the same time, recent theories (Di Lollo, Enns, & Rensink, 2000;Lamme, 2002;Lamme & Roelfsema, 2000) stress the importance of intracortical feedback and recurrent processing as necessary conditions for visual awareness.…”
Section: Notesmentioning
confidence: 99%
“…These studies have shown that inconsistent primes are able to mislead pointing movements in the wrong direction, such that the initial behavioral response is time-locked to the prime, first proceeds in the direction specified by the prime, and only then proceeds in the target direction (F. T. Schmidt, 2002;T. Schmidt, Niehaus, & Nagel, 2006;T.…”
Section: Motor Activation In Response Primingmentioning
confidence: 99%